PEMETAAN PERUBAHAN PENGGUNAAN LAHAN DI DESA CIBARUSAH KOTA UNTUK MENDUKUNG PENGELOLAAN LINGKUNGAN BERKELANJUTAN - Yuningsih, Cahya; Mulyadi, Acep; Maysaroh Chairunnisa, Nurlaila (An-Nizam, 2025)
Changing land use has become a critical concern in sustainable environmental management, particularly in peri-urban and rural areas experiencing rapid development. Cibarusah Kota Village, located in Bekasi Regency, has undergone substantial land use transformation influenced by urbanization and industrial expansion. This study aims to analyze these changes and their implications for environmental sustainability by applying Geographic Information System (GIS) technology. Remote sensing data and field surveys were utilized to capture the dynamics of land use over the past ten years, supported by the concept of science and technology diffusion to generate practical outputs for the local community. The findings indicate a significant reduction in agricultural land, accompanied by considerable growth in residential and industrial areas. This shift reflects the strong pressure of urban expansion on rural landscapes, leading to critical environmental challenges such as the reduction of open space, increased pollution risks, and potential loss of biodiversity. The results highlight the urgent need for integrated spatial planning and sustainable land management policies to balance economic development and environmental protection in Cibarusah Kota Village and similar peri-urban regions. Overall, this study provides valuable insights into the consequences of land use changes while offering a scientific basis for local decision-making.